STUDY OF MILK PROTEIN COMPOSITION AND COAGULATION PROPERTIES OF BURLINA LOCAL CATTLE BREED - Giovanni Niero; Mauro Penasa; Massimo De Marchi; Giulio Visentin; Martino Cassandro (Poljoprivreda, 2015)
Burlina is a dual-purpose cattle breed, mainly reared in mountain areas of Veneto Region (Italy). The aim of this study was to investigate milk protein composition and milk coagulation properties (MCP) of Burlina breed. A total of 80 individual milk samples were collected and milk casein fractions were detected and quantified with reversed-phase high-performance liquid chromatographic analysis whereas MCP were determined with Formagraph. Sources of casein fractions variation and MCP were investigated using a linear model including herd, parity, and days in milk as fixed effects. Casein fractions showed increasing concentrations across days in milk, but not specific trends across parities. Milk coagulation properties exhibited better values in early than late lactation stages. Also, they deteriorated across parities.